Integrated Community Interchanges Design Based on Interiority - Anugerah Nan Mulia (Architecture Department, Engineering Faculty, Universitas Diponegoro, 2023)
The rapid development of cities demands good and effective urban planning. However, poor planning results in lost space in various corners of the city, which actually has great potential to be developed and used properly. Seeing this phenomenon, the author is interested in exploring how to take advantage of the potential of lost space through urban interiority-based designs, with a focus on interchange designs in the middle of dense office and commercial areas.